Một phương pháp mới tìm khoảng mật độ hậu nghiệm cao nhất và ứng dụng - Lê Thanh Hoa; Phạm Hoàng Uyên; Nguyễn Đình Thiên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
In Bayesian Statistics, estimation of the credible interval  requires a different calculation formula from the confidence interval in Frequentist Statistics. Due to the complexity of the calculation, we propose a new method to find the highest posterior density interval through difference Dif., to effectively use the value of the quantile level and to save computation time. Specifically, we apply this technique to the closing stock price forecast of 16 stocks of large market price of Vietnam Stock Market and the first stocks in the alphabetical trading on HXN.
Keywords: Highest posterior density interval; Coverage interval; Forecast interval